(7y² + 6xy) - (-2xy + 3)
⇒ (-1 * -2xy) + (-1 * 3) = 2xy - 3
7y² + 6xy + 2xy - 3
7y² + 8xy - 3 Choice B.
Answer:
x and y = 0
the question looks weird and almost wrong because when you subtract the equations, you are left with nothing
Step-by-step explanation:
Multiply the top equation by 3 to make the -x a -3x instead.
Then do the top equation - the bottom equation
At this point you should be left with x
Answer: AB = 6
Step-by-step explanation:
If CD = 12 , AC also = 12
B is the midpoint of AC so one side = 6
AB is one side of AC , so AB = 6
I am not a professional, I am simply using prior knowledge!
Note- It would mean the world to me if you would mark me brainliest!
Answer:
Starting is 10 going up by 5x
Step-by-step explanation:
When you look at a graph there is a y and x axis's. 10 is on the y axis and its going up by 5x.